Iron Recycling of Slag for E.A.F Steelmaking by Solid Carbon - Khoshki, M.; Golmakani, M.H.; Momen Heravi, M. (Asian Journal of Chemistry, 2011)
Steelmaking slag from refining process both in oxygen converter and in electric arc furnaces contain a high portion of refined metallic iron-raw material. One of the most important applications for blast furnace and steelmaking slag is in cement production industry but high percent of iron-oxide in steelmaking slag can be useless for cement quality and also can wear the cement mills. Therefore, only demetallized slag could be useful and effective in cement factories. For this reason the first and very important process of steelmaking slag treatment is to divide the slag into two parts: a metallic one and a demetallized steelmaking slag. In this research, reports experimental studies on reduction of iron-oxide from a ternary FeO-SiO2-CaO slag with solid carbon. In this process, E.A.F slag with some supplements as same coke powder and flux were mixed and fused in graphite crucible. The results indicate that FeO recycling by solid carbon is completely successfully and at least 60 % has been reduced.